Direct Negotiation and the Impact on Supplier Performance - M. Halizahari; MD Faris (International Journal of Supply Chain Management, 2020)
This study explored the public procurement on the Direct Negotiation issues. There are various types of public procurements implemented in the Malaysian government procurement system, however, Direct Negotiation has become the contractors’ opportunities in abusing the system where many projects have failed to be completed as scheduled and others were completed with below standard which has not achieved the expectations. As stated in Ministry of Finance Circular 2013, the Direct Negotiation can only be awarded when there is urgent requirement, only for expert and credible contractor. This study has collected data from the Auditors General annual report from year 2015 until 2017, focuses mainly on auditor’s observation on Direct Negotiation issues. Despite many comments from the public on the corrupt practice in the public procurement, this study has identified that there might be non-compliance on the decision in appointing the contractor for the Direct Negotiation which many issues arise in Auditor General report were on inefficiency of the contractor which has defeated the purposes on awarding the project through Direct Negotiation to credible contractor. Therefore, this research has agreed and supported that in order to be transparent and open, the Malaysian Government should eliminate Direct Negotiation and apply open tender on all public procurement.